Locus of control and technology adoption in sub-Saharan Africa: Evidence from Ethiopia - Abay, Kibrom A.; Blalock, Garrick; Berhane, Guush (2017)
We investigate the implication of farmers’ locus of control on their technology adoption decisions. Our empirical analysis is based on two longitudinal surveys and hypothetical exercises conducted on Ethiopian rural farmers. We find that locus of control significantly predicts farmers’ technology adoption decisions, including use of chemical fertilizers, improved seeds, and irrigation. We show that individuals with an internal locus of control have higher propensity of adopting agricultural technologies, while those with an external locus of control seem less likely to adopt one or more of these agricultural technologies. These empirical regularities are observed in both datasets, and for both revealed measures of farmers’ technology adoption decisions as well as farmers’ hypothetical demand for a new agricultural technology. The results hold even in a more conservative fixed effects estimation approach, assuming locus of control as time-variant and dynamic behavioral trait. These results provide some psychological (behavioral) explanations to the existing empirical puzzle of the low levels of adoption of seemingly profitable agricultural technologies in Sub-Saharan Africa. Our results highlight that improving farmers’ psychological capital (non-cognitive skills) and providing commitment devices may facilitate agricultural transformation. More generally, the results suggest that anti-poverty policies that only focus on improving poor households’ external constraints, including physical access to markets and technologies, may not sufficiently alleviate agricultural underinvestment.